Evaluation the activity of Ajwa of date palm fruits extract as promoter rooting for stem cuttings of cassia (Cassia surattensis Berm). - S. Habib, Amal Abdul; J. Attiya, Hatim (Iraqi Journal of Science, 2022)
The present study was carried out in the nursery at Al – Dora (Baghdad). During spring 2015 under green hous conditions. The aim was to evaluate the effect of different concentration (0, 1.25 and 2.5) g./l of aqueous Ajwa date fruit extract on different cutting position (basal, sub terminal and terminal) for different dipping times (24, 48) hours, on cassia stem cuttings. After 2 months of planting the results showed that the 2.5 gm. /l of Ajwa date extract with basal cuttings for 48 dipping times accelerated the time of rooting to 3.7 weeks compared to 8 weeks in control treatment. This treatment increased rooting percentage to 77.7% compared to 0% in control treatment. It gave the highest value of both rooting numbers 2.2 per cutting and rooting lengths 2.89 cm. The results indicated that 2.5 gm./l of Ajwa date extract with sub terminal cuttings for 48 hours dipping times gave the highest results in leaves, leaflet numbers and leaflet area 2.88, 4.0 and 1.70 cm respectively. The analysis of ajwa date quantity showed the present of 50.38 and 48.82 μmole/g of catalase peroxidase enzymes respectively with the absence of IAA, GA3 and Zeatin hormones.